A IMPLEMENTAÇÃO DA LEI 10.639/2003 E A EDUCAÇÃO ÉTNICO-RACIAL: desafios e limitações - Nascimento, Weverton Freitas (2025)
In writing this article we sought to understand the contributions, limits and challenges of implementing Law 10.639/03. Metasynthesis seeks to create new understandings beyond primary studies with in-depth data analysis.To this end, we carried out a meta-synthesis based on a survey of works (dissertations and theses), using the BUSCAd tool - version 2.8.4. The Brazilian Digital Library of Theses and Dissertations (BDTD) and the Capes Catalogue of Dissertations and Theses were selected to search for works published between 2003 and 2023, and the terms “Ethnic-Racial Education”, “Pedagogical Practice” and “Law 10.639/2003” were used in conjunction. We obtained a corpus of 17 papers which were read, listed and mapped. The results show that the works analyzed contributed to verifying the existence of limiting factors, structural racism and epistemicide appear as mechanisms for the non-promotion and disqualification of Law 10.639/03 in school spaces. This produces weaknesses in teaching, the curriculum, training, capacity building and teaching materials. Aspects that influenced the understanding of the contributions and challenges of Law 10.639/03.